2018
DOI: 10.1371/journal.pone.0199488
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ preferred tree species and their potential carbon stocks in southern Burkina Faso: Implications for biocarbon initiatives

Abstract: The success of terrestrial carbon sequestration projects for rural development in sub-Saharan Africa lies in the (i) involvement of local populations in the selection of woody species, which represent the biological assets they use to meet their daily needs, and (ii) information about the potential of these species to store carbon. Although the latter is a key prerequisite, there is very little information available. To help fill this gap, the present study was undertaken in four pilot villages (Kou, Dao, Vras… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 55 publications
(62 reference statements)
1
12
0
2
Order By: Relevance
“…We compared the models developed in this study with four previously published models developed by Brown et al (1989), Chave et al (2005), Chave et al (2014), andJucker et al (2017). We choose these models for comparison with our own model because they are commonly used for biomass estimation in Burkina Faso by previous studies (Qasim et al 2016;Dimobe et al 2018d;Dimobe et al 2019). The general lack of agreement between the models developed for D. mespiliformis in this study and the generic models, can only be viewed as discouraging.…”
Section: Comparison With Previously Published Modelsmentioning
confidence: 93%
“…We compared the models developed in this study with four previously published models developed by Brown et al (1989), Chave et al (2005), Chave et al (2014), andJucker et al (2017). We choose these models for comparison with our own model because they are commonly used for biomass estimation in Burkina Faso by previous studies (Qasim et al 2016;Dimobe et al 2018d;Dimobe et al 2019). The general lack of agreement between the models developed for D. mespiliformis in this study and the generic models, can only be viewed as discouraging.…”
Section: Comparison With Previously Published Modelsmentioning
confidence: 93%
“…50 out of 217) address the relationships between agriculture and climate change in Burkina Faso or even single regions in the country e.g. north (Hänke et al, 2016;Kima et al, 2014;Rigolot et al, 2017), south (Borona et al, 2016;Dimobe et al, 2018), south-west (Fonta et al, 2015;Sanfo et al, 2017) and south-east (Mande et al, 2015).…”
Section: Bibliographical Metrics Of Research On Climate Change and Agriculture In Burkina Fasomentioning
confidence: 99%
“…Mutuo et al (2005) suggest that "Evidence is emerging that agroforestry systems are promising management practices to increase aboveground and soil C stocks and reduce soil degradation, as well as to mitigate greenhouse gas emissions" (p. 43). However, Dimobe et al (2018) underline that the success of carbon sequestration projects, including those involving agro-forestry, lies in the "involvement of local populations in the selection of woody species […] and information about the potential of these species to store carbon". Moreover, there are some doubts about whether carbon sequestration markets (cf.…”
Section: Climate Change Mitigation and Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mulberry, native to China, is of great economic importance as the sole food of the mulberry silkworm moth (Bombyx mori L.) and as a source of timber, fuelwood, fodder, food, drinks, medicines, constituents of cosmetics, etc. (Qin et al 2012;Gozlekci et al 2015;Dimobe et al 2018). Recently, Li et al (2020) found that the photosynthetic carbon sink of mulberry is greater compared to the total carbon emission, which indicates a beneficial effect for the environment.…”
Section: Introductionmentioning
confidence: 99%